Reference Standard of Serum Neopterin Concentration in Healthy Children - Plata-Nazar Katarzyna (Pteridines, 2007)
Introduction: Increased neopterin concentrations are observed in many diseases in which cell immunity is stimulated. A quick and sensitive method for monitoring the changes in immune system can be useful for understanding etiopathogenesis of the disease and choosing the appropriate treatment. There are only few known data concerning normal serum neopterin value in children, therefore the wide clinical use of this parameter is limited.